Readily releasable vesicles recycle at the active zone of hippocampal synapses - Schikorski, Thomas (National Academy of Sciences, 2014)
During the synaptic vesicle cycle, synaptic vesicles fuse with the plasma membrane and recycle for repeated exo/endocytic events. By using activity-dependent N-(3-triethylammoniumpropyl)-4-(4-(dibutylamino) styryl) pyridinium dibromide dye uptake combined with fast (<1 s) microwave-assisted fixation followed by photoconversion and ultrastructural 3D analysis, we tracked endocytic vesicles over time, “frame by frame.” The first retrieved synaptic vesicles appeared 4 s after stimulation, and these endocytic vesicles were located just above the active zone. Second, the retrieved vesicles did not show any sign of a protein coat, and coated pits were not detected. Between 10 and 30 s, large labeled vesicles appeared that had up to 5 times the size of an individual synaptic vesicle. Starting at around 20 s, these large labeled vesicles decreased in number in favor of labeled synaptic vesicles, and after 30 s, labeled vesicles redocked at the active zone. The data suggest that readily releasable vesicles are retrieved as noncoated vesicles at the active zone.